1989
DOI: 10.1109/22.21615
|View full text |Cite
|
Sign up to set email alerts
|

Physical modeling of GaAs MESFETs in an integrated CAD environment: from device technology to microwave circuit performance

Abstract: -A CAD environment leading from technology to performance evaluation by integrating process, device, and circuit simulation would be a valuable tool for the development of monolithic microwave circuits. The paper focuses on the linkage between a physical device simulator for smalland large-signal characterization, and CAD tools for both linear and nonlinear circuit analysis and design. Efficient techniques are presented for the physical dc and small-signal analysis of MESFETs; then, the problem of physical sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…In accordance with other case studies [44], good agreement is found with measured dc data, although the substrate residual donor and acceptor concentrations had to be reverse-modelled so as to match the threshold voltage exactly. The ac model had to include low-frequency dispersion effects due to substrate deep levels, without which the output conductance would have been underestimated by a factor 2.…”
Section: E Examplessupporting
confidence: 70%
“…In accordance with other case studies [44], good agreement is found with measured dc data, although the substrate residual donor and acceptor concentrations had to be reverse-modelled so as to match the threshold voltage exactly. The ac model had to include low-frequency dispersion effects due to substrate deep levels, without which the output conductance would have been underestimated by a factor 2.…”
Section: E Examplessupporting
confidence: 70%
“…The shortterm memory requirement is commonly verified for "intrinsic" devices, i.e., devices not affected by dominating parasitic effects. Such a case occurs in physics-based models, wherein parasitics can be exactly deembedded [14]. Actually, a number of validation tests have shown good agreement between 2-D simulated LS responses and the corresponding values predicted according to (8).…”
Section: Ls Sensitivity Under Periodic Excitation Through Intermmentioning
confidence: 99%
“…In particular, according to the approach in [2], [14], the LS circuit analysis is carried out through circuit-oriented nonlinear models and their characteristic parameters are extracted from dc and small-signal ac physics-based device simulations. In this way, LS circuit analysis is performed with good computational efficiency, while the link between physical parameters and the corresponding circuit performance is still provided by an off-line, physics-based device sensitivity analysis.…”
Section: Ls Sensitivity Under Periodic Excitation Through Intermmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for this is the severe voltage dependence [1,2] of the intrinsic transistor equivalent-circuit elements, which represent the physical properties of the semiconductor substrate. Therefore, in actual practice, a constant voltage regulator is used typically when assembling such an oscillator.…”
Section: Introductionmentioning
confidence: 99%